Increasing Character Education in Learning Sundanese Script in Elementary Schools (SD Negeri Depok Baru 3) Depok City - Iis Gustini; Nika Sintesa; Valentina Happy Vanesa (Indonesian Journal of Research and Service Studies, 2024)
Learning Sundanese script which is packaged in the SARASA (A Day with Sundanese Literacy) Program is an effort made to improve the character education profile of Pancasila students, namely independent, creative and globally diverse. Apart from that, after conducting research, this activity also aims to introduce and preserve Sundanese script to students, especially elementary school students, as well as increasing students' love of regional culture, especially Sundanese culture at SD Negeri Depok Baru 3. The SARASA program is packed with activities that are interesting, fun, pro-student and foster student agency in students. Apart from learning Sundanese script, students are also introduced to traditional West Javanese songs and games.